(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
The malignant transformation of oral potentially malignant disorders (OPMDs) into oral squamous cell carcinoma (OSCC) has traditionally been viewed through the narrow lens of host genomic instability and cumulative environmental mutagenesis. However, the diagnostic paradigm is currently undergoing a profound shift. Advanced multi-omics sequencing has unveiled a vast, highly active oral microecosystem that does not merely colonise neoplastic tissue opportunistically, but actively orchestrates the aetiopathogenesis of the tumour. This review exhaustively examines the transition from microbial haemostasis to pathogenic dysbiosis within OPMDs. By mapping the specific mechanisms through which keystone periopathogens—namely Fusobacterium nucleatum and Porphyromonas gingivalis—induce the epithelial-mesenchymal transition (EMT), hyperactivate inflammatory signalling cascades, and subvert local immune surveillance, this manuscript provides a comprehensive molecular framework. Integrating microbial landscaping into routine oral pathology offers profound new avenues for predicting malignant transformation and designing targeted microecological therapies.